Alterations in novel inflammatory biomarkers during perioperative cardiovascular surgeries involving cardiopulmonary bypass: a retrospective propensity score matching study - Zhou, Wei; Wang, He; Li, Chen; Ma, Qi-min; Gu, Yan-hui; Sheng, Shu-yue; Ma, Shao-lin; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2024)
Background: Cardiopulmonary bypass (CPB) brings strong inflammatory response to cardiovascular surgery patients in perioperative period. This article mainly focuses on the perioperative application of novel inflammatory biomarkers in cardiovascular surgery undergo CPB.Methods: Patients were divided into CPB group and non-CPB group according to whether they underwent CPB during cardiovascular surgery. The novel inflammatory biomarkers and clinical results were recorded. Neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), platelet × neutrophil/lymphocyte ratio (SII) and monocyte × platelet × neutrophil/lymphocyte ratio (PIV) were calculated. Primary outcomes were perioperative prognosis between CPB group and non-CPB group.Results: A total of 332 patients were initially included in the study. Before PSM, there were 96 patients in the CPB group and 236 patients in the non-CPB group. After PSM, there were 58 patients in the both groups. Compared with the non-CPB group, the CPB group had a higher proportion of intraoperative transfusion of blood products (63.79% vs 6.90%, P<0.001), both red blood cells (58.62% vs 3.45%, P<0.001) and plasma (41.38% vs 1.72, P<0.001), a higher drainage fluid within 24h (380[200,550] vs 200[24,330], ml P=0.002), and required longer mechanical ventilation time (14.